2000
DOI: 10.4049/jimmunol.165.11.6653
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Epitope-Containing Hypoallergenic Recombinant Fragments of the Major Birch Pollen Allergen, Bet v 1, Induce Blocking Antibodies

Abstract: Allergen-specific immunotherapy represents one of the few curative approaches toward type I allergy. Up to 25% of allergic patients are sensitized against the major birch pollen allergen, Bet v 1. By genetic engineering we produced two recombinant (r) Bet v 1 fragments comprising aa 1–74 and aa 75–160 of Bet v 1, which, due to a loss of their native-like fold, failed to bind IgE Abs and had reduced allergenic activity. Here we show that both fragments covering the full Bet v 1 sequence induced human lymphoprol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
84
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 55 publications
9
84
0
2
Order By: Relevance
“…Results obtained with blocking rabbit IgG Abs may in fact be applicable for immunotherapy. We found that immunization of mice with hypoallergenic derivatives of the major birch pollen allergen, Bet v 1, using schemes that are used for immunotherapy of allergic patients, yielded comparable results as the immunization of rabbits (31,32). The ability of unfolded hypoallergenic allergen derivatives to induce IgG Abs that inhibit the binding of patients' IgE directed to conformational epitopes may be explained in two ways.…”
Section: Discussionmentioning
confidence: 96%
“…Results obtained with blocking rabbit IgG Abs may in fact be applicable for immunotherapy. We found that immunization of mice with hypoallergenic derivatives of the major birch pollen allergen, Bet v 1, using schemes that are used for immunotherapy of allergic patients, yielded comparable results as the immunization of rabbits (31,32). The ability of unfolded hypoallergenic allergen derivatives to induce IgG Abs that inhibit the binding of patients' IgE directed to conformational epitopes may be explained in two ways.…”
Section: Discussionmentioning
confidence: 96%
“…One disadvantage of SIT is that the administration of allergenic material may cause severe and lifethreatening anaphylactic side effects (1). This problem can be bypassed by using isoforms of allergens (2), deletion mutants (3), fragments of proteins (4,5), or linear peptides (6) that lack the original IgE-binding epitopes. The use of engineered "hypoallergenic" variants with reduced IgE reactivity is now being explored in several systems (7,8).…”
mentioning
confidence: 99%
“…The presence of conformational B cell epitopes proposed a novel approach to reduce IgE binding by fragmentation [24] and oligomerization of one allergen or hybridization of several allergens [25,26]. The majority of Ab elicited by exposure to native protein antigens recognize conformation-dependent, discontinuous epitopes [2,12,27], which is confirmed using mouse mAb against Api m 1 and Api m 2.…”
Section: Discussionmentioning
confidence: 93%